Umrah COD and Its Legal Standing in Islamic Law: Navigating Contractual Innovation in Contemporary Worship Economy - Ismail, Ahmad; Nur, Salahuddin; Alfadil S., Muhamimin (MUI Sulawesi Selatan, 2024)
This study aims to examine the legal status and operational mechanisms of the Umrah Cash on Delivery (COD) system within the framework of Islamic jurisprudence. As digital technologies reshape the landscape of religious travel, the emergence of Umrah COD—where payment is made after the delivery of travel documents or services—presents both innovative solutions and potential juridical challenges. Using a qualitative-descriptive method, the research relies on document analysis, including fiqh texts, contemporary fatwas, and digital platform policies. It investigates the compatibility of Umrah COD with sharia principles, particularly regarding contractual obligations, gharar (uncertainty), and consumer protection. Findings reveal that Umrah COD may be considered permissible under Islamic law if the contract fulfills core conditions such as mutual consent, clarity of terms, and absence of deception. The role of digital platforms in facilitating transparency and accountability is also emphasized as a supporting factor in ensuring sharia compliance. This study contributes original insights by addressing a relatively underexplored intersection between digital commerce and religious travel through a fiqh-based lens. The implications are significant for regulators, travel agents, and Muslim consumers, offering guidance for developing ethically sound and legally valid practices in the evolving Umrah economy.